The marsh crab, Sartoriana rokitanskyi (Pretzmann, 1971) (Decapoda, Brachyura, Gecarcinucidae) from southern Iran - Kamrani, Ehsan; Ng, Peter K. L.; Mirzadeh, Mehrnoush; Nakhodai, Sahar (Zootaxa, 2009)
The marsh crab, Sartoriana rokitanskyi (Pretzmann, 1971) (Brachyura, Gecarcinucidae), is recorded from near a hot spring in Geno, southern Iran. The taxonomy of the species, including differences with the allied S. blanfordi (Alcock, 1909), is discussed. Notes on its ecology are also provided.